Pengaruh Dana Pihak Ketiga, Pdrb, Bi Rate, Inflasi Dan Npl Terhadap Perkembangan Penyaluran Pembiayaan Bpr Dan Bpr Syariah Di Provinsi Jawa Tengah (Periode September 2011 - Desember 2014) - Putri, Fajar Pardanny; , Drs. Yuni Prihadi Utomo, MM; , Drs. Jazuli, M.Pi (2015)
This study aims to determine the effect of third party funds (DPK), Gross Domestic Product (GDP), interest rate (BI Rate), inflation and non-performing loan (NPL) on the distribution of funding BPR and BPR Syariah in Central Java province in the period September 2011 - December 2014, the analytical techniques used in this research is multiple linear regression (OLS). The data used is the time series data and secondary data published by Bank Indonesia and BPS Central Java, the sample includes 164 BPR Sharia and 252 Conventional BPR. Based on the research results DPK significant positive effect and significant positive effect on GDP in the finance portfolio Conventional BPR and BPR Syariah, while inflation, BI Rate, NPL or NPF no significant effect on the distribution of funding BPR Conventional and BPR Sharia in the province of Central Java period September 2011 - December 2014.